TDP‐43 Proteinopathy Presenting with Typical Symptoms of Parkinson's Disease. Issue 7 (9th May 2022) - Yamashita, Rika; Beck, Goichi; Yonenobu, Yuki; Inoue, Kimiko; Mitsutake, Akihiko; Ishiura, Hiroyuki; Hasegawa, Masato; Murayama, Shigeo; Mochizuki, Hideki
Abstract : Accumulation of abnormal transactivation response DNA‐binding protein of 43 kDa (TDP‐43) independently induces dopaminergic neuronal loss in the substantia nigra without Lewy pathology, and results in typical Parkinson's disease‐like motor symptoms.